2021
DOI: 10.1101/2021.02.08.430375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of NADP+-reducing enzymes inEscherichia colicentral metabolism via adaptive evolution

Abstract: The nicotinamide cofactor specificity of enzymes plays a key role in regulating metabolic processes and attaining cellular homeostasis. Multiple studies have used enzyme engineering tools or a directed evolution approach to switch the cofactor preference of specific oxidoreductases. However, whole-cell adaptation towards the emergence of novel cofactor regeneration routes was not previously explored. To address this challenge, we used an Escherichia coli NADPH-auxotroph strain. We continuously cultivated this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…More generally, specificity for NAD(H) or NADP(H) for some enzymes can strongly influence intracellular reaction flux distributions (10), serving as the basis for metabolic engineering strategies to dramatically improve yields of valuable metabolic byproducts (10, 1618). Importantly, recent work has demonstrated that specificity for NAD(P)H can emerge in laboratory evolution studies, suggesting that coenzyme preference might be a highly adaptable feature of metabolic networks (19). However, it is unclear if most enzymes are typically constrained to use only NAD(H) or NADP(H), and whether a single coenzyme could support the functioning of metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, specificity for NAD(H) or NADP(H) for some enzymes can strongly influence intracellular reaction flux distributions (10), serving as the basis for metabolic engineering strategies to dramatically improve yields of valuable metabolic byproducts (10, 1618). Importantly, recent work has demonstrated that specificity for NAD(P)H can emerge in laboratory evolution studies, suggesting that coenzyme preference might be a highly adaptable feature of metabolic networks (19). However, it is unclear if most enzymes are typically constrained to use only NAD(H) or NADP(H), and whether a single coenzyme could support the functioning of metabolism.…”
Section: Introductionmentioning
confidence: 99%